Tasquinimod modulates suppressive myeloid cells and enhances cancer immunotherapies in murine models - Shen, Li (Cancer Immunol Res, 2014)
A major barrier for cancer immunotherapy is the presence of suppressive cell populations in cancer patients, such as myeloid-derived suppressor cells (MDSC) and tumor-associated macrophages (TAM), which contribute to the immunosuppressive microenvironment that promotes tumor growth and metastasis. Tasquinimod is a novel antitumor agent that is currently at an advanced stage of clinical development for treatment of castration-resistant prostate cancer. A target of tasquinimod is the inflammatory protein S100A9, which has been demonstrated to affect the accumulation and function of tumor-suppressive myeloid cells. Here, we report that tasquinimod provided a significant enhancement to the antitumor effects of two different immunotherapeutics in mouse models of cancer: a tumor vaccine (SurVaxM) for prostate cancer and a tumor-targeted superantigen (TTS) for melanoma. In the combination strategies, tasquinimod inhibited distinct MDSC populations and TAMs of the M2-polarized phenotype (CD206(+)). CD11b(+) myeloid cells isolated from tumors of treated mice expressed lower levels of arginase-1 and higher levels of inducible nitric oxide synthase (iNOS), and were less immunosuppressive ex vivo, which translated into a significantly reduced tumor-promoting capacity in vivo when these cells were co-injected with tumor cells. Tumor-specific CD8(+) T cells were increased markedly in the circulation and in tumors. Furthermore, T-cell effector functions, including cell-mediated cytotoxicity and IFNγ production, were potentiated. Taken together, these data suggest that pharmacologic targeting of suppressive myeloid cells by tasquinimod induces therapeutic benefit and provide the rationale for clinical testing of tasquinimod in combination with cancer immunotherapies.